Neurovascular examination : the rapid evaluation of stroke patients using ultrasound waveform interpretation - Alexandrov, Andrei V. (Wiley-Blackwell, 2013)
The use of neurovascular ultrasound is of increasing importance in neurological practice, both for radiologists and increasingly by neurologists themselves. Written by the world's most renowned expert, this book explainsultrasound examination of a stroke patient scanning protocols interpretation of the results Case examples (with a standard template presentation correlating presentation to waveform output) reinforce the book's practical nature. Illustrated with photos of the tests, explanations, and with actual waveforms, images, and resu.